Risperidone and Olanzapne in-patient Utilization in the University of Malaya Medical Centre, Kuala Lumpur - Sulaiman, Ahmad Hatim; Yen, T.H. (Faculty of Medicine, University of Malaya, 2006)
The objective of this study was to compare in-patient drug use patterns, costs, and outcomes associated with risperidone or olanzapine in a naturalistic clinical setting. Retrospective chart reviews of 92 patients with psychotic disorders were conducted at the University of Malaya Medical Centre (UMMC). Data was collected from patients who were hospitalized and for whom risperidone or olanzapine was the drug of first choice for long-term pharmacologic treatment. Proportion of patients for whom efficacy of the studied treatment could be established (as rated by the treating physician) was higher, but not significantly, with risperidone compared to olanzapine (p = 0.46). The average dose of the studied medication was 2.9 ± 1.0 mg/day for risperidone and 9.7 ± 2.4 mg/day for olanzapine. The total cost was significantly higher (p <0.0001) for olanzapine (RM140.40; 95% CI: 108.4–181.9)compared to risperidone (RM50.80, 95% CI: 39.5–65.3). The daily cost was also significantly higher for olanzapine (RM19.16; 95% CI: 17.72–20.72) compared to risperidone RM4.95; 95% CI: 4.46–5.51, p < 0.0001). Analysis of responders showed significantly higher daily and total costs of treatment with olanzapine compared to risperidone. These preliminary data suggest that treatment with risperidone may be more costeffective than treatment with olanzapine. However, a longer duration of study and more data is needed before a proper conclusion on cost-effectiveness is made.